Development and Validation of the Lupus Impact Tracker: A Patient‐Completed Tool for Clinical Practice to Assess and Monitor the Impact of Systemic Lupus Erythematosus. Issue 10 (October 2014) - Jolly, Meenakshi; Garris, Cindy P.; Mikolaitis, Rachel A.; Jhingran, Priti M.; Dennis, Greg; Wallace, Daniel J.; Clarke, Ann; Dooley, Mary Anne; Parke, Ann; Strand, Vibeke; Alárcon, Graciela S.; Kosinski, Mark
<x xml:space="preserve">Abstract</x> Objective To derive and validate a brief patient‐completed instrument, the Lupus Impact Tracker (LIT), to assess and monitor the impact of systemic lupus erythematosus (SLE). Methods Items for the LIT were selected from the LupusPRO, a validated patient‐reported outcomes measure, using 3 approaches: confirmatory factor analysis (CFA), stepwise regression, and patient focus groups. CFA was conducted to find items from the LupusPRO that fit a unidimensional structure to allow scoring as a single index. Stepwise regression methods identified items with the strongest relationship (convergent validity) with disease activity measures and patient health rating. Focus groups (n = 26 patients) identified the most important items describing SLE impact. Selected items were evaluated for reliability and validity. Results CFA found 21 items that fit a unidimensional structure. Stepwise regressions identified 15 of 21 items having good convergent validity with clinical measures. Patient focus groups identified 9 of 15 items as best capturing the impact of SLE. Overall, 7 items were selected across all 3 approaches (CFA, stepwise regression, and focus groups). Another 15 items were selected across 2 approaches. Through consensus with rheumatology clinician experts, a final set of 10 items was selected for the LIT. The LIT items showed good internal consistency (0.89) and test–retest reliabilities (0.87). Mean LIT scores differed significantly (P < 0.05) across criterion groups in the hypothesized direction, providing evidence of discriminant validity and responsiveness. Conclusion The LIT is reliable and valid in SLE patients and offers a practical way for physicians and patients to assess and monitor the impact of SLE.